Group method of data handling in technical diagnostic tasks - Kuś, Janusz; Banaszak, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
The work presents a certain concept of an advisory system, which assists in making decisions in the technical diagnostic tasks. To this end, as a mathematical formalizm, the Group Method of Data Handling (GMDH), from the class of genetic algorithms has been adopted.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka